PENGARUH KEMAMPUAN PERSEPTUAL, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL (PNS) DINAS PENDIDIKAN KABUPATEN BOJONEGORO - Firdaus, Muhammad Ainul; Fitriyah, Anik (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2021)
The objectives to be achieved in this study are to describe the perceptual ability, work motivation, work discipline on the Performance of Civil Servants (PNS) of the Bojonegoro Regency Education Office, to test and analyze perceptual abilities, work motivation and work discipline on the Performance of Civil Servants (PNS). Bojonegoro District Education Office. The population in this study were all Civil Servants (PNS) at the Bojonegoro Regency Education Office who assessed 60 people with a sample of 60 people. Total sampling technique or census sampling. The analytical method used is multiple linear regression. Based on the results of research and discussion, perceptual ability, work motivation, work discipline and the performance of the Civil Servants (PNS) of the Bojonegoro Regency Education Office are in good categories. Perceptual ability has a positive and significant effect on the Performance of Civil Servants (PNS) of the Bojonegoro Regency Education Office. Work motivation has no effect on the performance of Civil Servants (PNS) of the Bojonegoro Regency Education Office. Work discipline has a significant effect on the performance of the Civil Servants (PNS) of the Bojonegoro Regency Education Office.